In vivo noninvasive visualization of retinal perfusion dysfunction in murine cerebral malaria by camera‐phone laser speckle imaging. Issue 1 (27th July 2018) - Remer, Itay; Pierre‐Destine, Lorraine F.; Tay, David; Golightly, Linnie M.; Bilenca, Alberto
Abstract : Cerebral malaria (CM) is a severe complication of Plasmodium falciparum infection associated with impaired cerebral blood flow. Visualization of the eye vasculature, which is embryologically derived from that of the brain, is used clinically to diagnose the syndrome. Here, we introduce camera‐phone laser speckle imaging as a new tool for in vivo, noncontact two‐dimensional mapping of blood flow dynamics in the experimental cerebral malaria (ECM) murine model of Plasmodium berghei ANKA. In a longitudinal study, we show that the camera‐phone imager can detect an overall decrease in the retinal blood‐flow‐speed (BFS) as ECM develops in P. berghei ANKA infected mice, with no similar change observed in uninfected control mice or mice infected with a non‐ECM inducing strain ( P. berghei NK65). Furthermore, by analyzing relative alterations in the BFS of individual retinal vessels during the progression of ECM, we illustrate the strength of our imager in identifying different BFS‐change heterogeneities in the retinas of ECM and uninfected mice. The technique creates new possibilities for objective investigations into the diagnosis and pathogenesis of CM noninvasively through the eye. The camera‐phone laser speckle imager along with measured spatial blood perfusion maps of the retina of a mouse infected with P. berghei ANKA—a fatal ECM model—on different days during the progression of the infection (top, day 3 after infection; middle, day 5 after infection; and bottom, day 7 after infection). Abstract : Cerebral malaria (CM) is a severe complication of malaria associated with impaired cerebral blood flow. Here, camera‐phone laser speckle imaging is introduced as a new tool for in vivo, noncontact two‐dimensional mapping of heterogeneous blood flow dynamics in murine CM. The camera‐phone imager is shown to be useful in detecting the overall decrease in the retinal blood‐flow‐speed as CM develops in mice, with no similar change observed in control mice.